Cyclooxygenase-2 Expression Is Related With Localization, Proliferation, and Overall Survival in Canine Melanocytic Neoplasms - Martínez, C. M.; Peñafiel-Verdú, C.; Vilafranca, M.; Ramírez, G.; Méndez-Gallego, M.; Buendía, A. J.; Sánchez, J. (Veterinary pathology, 2011)
A direct relationship has been firmly established between cyclooxygenase-2 (COX-2) expression and malignant behavior in human melanoma. This report examines the relationship between COX-2 expression and tumor location, mitotic and proliferative indices, degree of T CD3+ lymphocyte infiltration, overall survival, and frequency of recurrence and metastasis of 57 melanocytic tumors (25 oral and 32 cutaneous). COX-2 was highly or moderately expressed in 88% of oral neoplasms (22 of 25), whereas for their cutaneous counterparts, COX-2 expression was low or insignificant in 75% of cases (24 of 32). High and moderate COX-2 expression levels were observed in 73% of melanocytic tumors with a mitotic index ≥ 3 per 10 high-power fields (26 of 36), whereas in 81% of tumors with a mitotic index < 3 (17 of 21), expression was mild or absent. There were 41 cases with known clinical outcomes; of those showing high, moderate, and mild COX-2 expression, 83.3% (10 of 12), 37.5% (3 of 8), and 25% (2 of 8) died, respectively, whereas 100% of animals showing no COX-2 expression (13 of 13) were still alive at the last follow-up. COX-2 expression was statistically correlated with tumor location, mitotic and percentage Ki-67 proliferative indices, and overall survival, frequency of neoplastic recurrence and metastasis. Regression analysis also showed disease-specific predictive value for COX-2 expression for subjects with melanocytic neoplasms. Additionally, only high COX-2 expression showed significant differences in overall survival, in comparison with moderate, mild, or absent expression. These results suggest that high COX-2 expression may be considered a prognostic biomarker and potentially as a target for therapeutic and preventive strategies in canine melanocytic neoplasms.